The Interplay of Individual Differences and Explicit Pragmatic Input on the Effectiveness of EFL Learners’ Grammar Development - Adam, Sutisno; Sailuddin, Sartika Putri; Maricar, Farida (Institut Agama Islam Negeri (IAIN) Kendari, 2026)
This study explored the impact of explicit pragmatic input instruction on grammatical development among intermediate-level English as a Foreign Language (EFL) learners, focusing on the moderating role of individual differences, including cognitive ability and learning preferences. Conducted with 65 university students enrolled in a compulsory grammar course, they were randomly assigned to either an experimental group receiving instruction that integrated pragmatic functions within grammar teaching or a control group receiving traditional form-focused grammar instruction. Pre- and post-tests assessed grammatical proficiency, while cognitive ability and learning preferences were measured to evaluate their influence on learning outcomes. Quantitative analyses, including paired-samples t-tests, repeated-measures ANOVA, and hierarchical regression, revealed that the experimental group exhibited significantly greater grammatical improvements than the control group. Moreover, learners with higher cognitive abilities and visual or kinesthetic learning preferences benefited more substantially from explicit pragmatic input instruction. Qualitative data from interviews and classroom observations complemented these findings by highlighting increased learner engagement, motivation, and pragmatic awareness in the experimental group. Participants reported that pragmatic-contextualized activities fostered meaningful grammar learning and practical application in communication, in contrast to the more mechanical learning experiences of the control group. The results underscore the effectiveness of integrating pragmatic input with grammar instruction and emphasize the need to tailor teaching approaches to individual learner profiles. The implications for EFL pedagogy include adopting multimodal, context-rich grammar teaching strategies to enhance communicative competence. This study contributes to advancing evidence-based practices that bridge grammatical knowledge and pragmatic use in diverse contexts of language learning.